Development of the neurons controlling fertility in humans: new insights from 3D imaging and transparent fetal brains. - Casoni, F; Malone, SA; Belle, M; Luzzati, F; Collier, F; Allet, C; Hrabovszky, E; Rasika, S; Prevot, V; Chédotal, A; Giacobini, P (The Company of Biologists, 2016)
Fertility in mammals is controlled by hypothalamic neurons that secrete gonadotropin-releasing hormone (GnRH). These neurons differentiate in the olfactory placodes during embryogenesis and migrate from the nose to the hypothalamus before birth. Information regarding this process in humans is sparse. Here, we adapted new tissue-clearing and whole-mount immunohistochemical techniques to entire human embryos/fetuses to meticulously study this system during the first trimester of gestation in the largest series of human fetuses examined to date. Combining these cutting-edge techniques with conventional immunohistochemistry, we provide the first chronological and quantitative analysis of GnRH neuron origins, differentiation and migration, as well as a 3D atlas of their distribution in the fetal brain. We reveal not only that the number of GnRH-immunoreactive neurons in humans is significantly higher than previously thought, but that GnRH cells migrate into several extrahypothalamic brain regions in addition to the hypothalamus. Their presence in these areas raises the possibility that GnRH has non-reproductive roles, creating new avenues for research on GnRH functions in cognitive, behavioral and physiological processes.